2014
DOI: 10.7763/ijmmm.2014.v2.104
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nano Calcium Carbonate Production Process Using Taguchi Method

Abstract: Abstract-This paper presents optimization of nano calcium carbonate production parameters to achieve the optimum production rate by using Taguchi method. The combination of optimum level of process parameters was obtained by using the analysis of signal-to-noise (S/N) ratio. The level of importance of the process parameters on production rate was determined by using analysis of variance (ANOVA). It was found that the optimum level of process parameters are solution flow rate of 9 lit/min, gas flow rate of 20 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Al-Refaie et al (2013) discussed the optimization of multiple fuzzy responses by applying fuzzy regression and desirability function in Taguchi methodology. Pour, and Moghadam (2014) used the Taguchi approach in the nano-calcium carbonate optimization to determine the best manufacturing level. Experimental results showed that the utmost echelon of process factors was a gas flow rate of 20 liters/minutes, 9 liters/minutes of solution flow rate, and a solution concentration of 70 g/litres.…”
Section: Single Optimization Methodsmentioning
confidence: 99%
“…Al-Refaie et al (2013) discussed the optimization of multiple fuzzy responses by applying fuzzy regression and desirability function in Taguchi methodology. Pour, and Moghadam (2014) used the Taguchi approach in the nano-calcium carbonate optimization to determine the best manufacturing level. Experimental results showed that the utmost echelon of process factors was a gas flow rate of 20 liters/minutes, 9 liters/minutes of solution flow rate, and a solution concentration of 70 g/litres.…”
Section: Single Optimization Methodsmentioning
confidence: 99%
“…The mean value of the com pressive strength corresponding to the optimum conditions was obtained as 160.17 kg/cm -2 , which fell within the predicted range. In the research work of Pour [26] , by studying the effects of the nano calcium carbonate production parameters on the production rate using the Taguchi method, the optimum level of production parameters and their priority for achieving optimum production rate was investigated. The most important parameters that governed production process of nano calcium carbonate were discovered to be the solution flow rate, gas flow rate and the solution concentration.…”
mentioning
confidence: 99%